A Retrospective Case Series on Free Flap Reconstruction for Ischemic Diabetic Foot: The Nutrient Flap Further Explained. Issue 6 (15th April 2022) - Kwon, Jin Geun; Cho, Min-Jeong; Pak, Changsik John; Suh, Hyunsuk Peter; Hong, Joon Pio
Abstract : Background: This retrospective case series compares the outcomes and postoperative oxygen levels in patients who underwent free flap versus primary closure/local flap reconstruction for ischemic diabetic foot wounds to determine the influence of free flap on the surrounding ischemic tissues. The authors hypothesized that the free flap would benefit the surrounding ischemic tissue as a nutrient flap by increasing the tissue oxygen content. Methods: The patients were divided into two groups: group 1 underwent free flap reconstruction, and group 2 underwent partial foot amputation with primary closure/local flap. Patient demographics, endovascular intervention, surgical outcome, postreconstruction intervention, and prereconstruction and postreconstruction transcutaneous oximetry were analyzed. Results: Among 54 patients, 36 were in group 1 and 18 were in group 2. There were no differences in patient demographics between the two groups. All patients had successful angioplasty. Statistical significance was noted in postreconstruction intervention in which group 2 required 2.8 ± 2.9 débridements (versus 1.2 ± 2.5 for group 1) and seven of 18 below-knee amputations (versus three of 36 for group 1) ( p < 0.05). Transcutaneous partial pressure of oxygen levels were significantly higher in group 1 at 6 months after reconstruction (61.6 ± 7.5 versus 32.6 ± 5.8 mmHg) ( p < 0.01). Conclusion: This study shows that the role of the free flap in ischemic diabetic limb may expand beyond that of providing coverage over the vital structures, and it supports the use of the free flap as a nutrient to increase oxygen content in the ischemic diabetic foot. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.